2012
DOI: 10.4084/mjhid.2012.010
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pleural Effusions due to Pulmonary Amyloidosis as the Presenting Manifestation of Multiple Myeloma

Abstract: Multiple Myeloma is a hematologic malignancy of plasma cell origin. Pleural effusion may develop in the setting of myeloma due to various reasons but is extremely uncommon as a presenting symptom. A 69-year-old Caucasian man presented with pleural effusions of undetermined etiology after extensive work up, and multiple failed pleurodesis. Lung biopsy revealed pulmonary amyloidosis and led to the diagnosis of multiple myeloma. Patient was started on chemotherapy but died within 6 weeks of his diagnosis due to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Agarwall et al demonstrated that in their case; the pleural fluid cytology did not reveal any myelomatous cell, and the recurrent effusions were secondary to pulmonary amyloidosis. 16 In our case, plasmocytoma diagnosis was confirmed by biopsy from the mass on ribs, whereas pleural involvement of multiple myeloma was detected by using flow cytometry of pleural fluid.…”
Section: Discussionmentioning
confidence: 53%
“…Agarwall et al demonstrated that in their case; the pleural fluid cytology did not reveal any myelomatous cell, and the recurrent effusions were secondary to pulmonary amyloidosis. 16 In our case, plasmocytoma diagnosis was confirmed by biopsy from the mass on ribs, whereas pleural involvement of multiple myeloma was detected by using flow cytometry of pleural fluid.…”
Section: Discussionmentioning
confidence: 53%
“…A total of 95 articles published over a period of 63 years were included, representing a final sample of 196 patients with PA. Figure 1 shows the flow chart of the article selection process. [ 8 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 <...…”
Section: Resultsmentioning
confidence: 99%
“…However, they can present with a variety of pulmonary symptoms that include, but not limited to, shortness of breath, wheezing, recurrent pneumonia, cough, hemoptysis and even pleural effusions. 5,6 For definitive diagnosis of amyloidosis, histologic evidence is required. Although often transbronchial biopsy is a safe and effective method for diagnosis, it is diagnostic in only approximately 60% of cases.…”
Section: Clinical Discussionmentioning
confidence: 99%